Cu-mediated grain boundary engineering in Nd–Ce–Fe–B nanostructured permanent magnets. (August 2022) - Tao, Y.M.; Jin, J.Y.; Zhao, L.Z.; Liu, X.L.; Zhang, Z.H.; Bai, G.H.; Wu, C.; Greneche, J.M.; Lv, K.; Xin, B.; Yan, M.
Abstract: Grain boundary (GB) engineering is of general significance for developing high-performance permanent magnets (PMs), but remains largely lacking in Nd–Ce–Fe–B nanostructured PMs containing the novel REFe2 (1:2, RE = rare earth) phase, previously considered as a coercivity-damaging agglomerated paramagnetic precipitate. Here we present a Cu-mediated GB engineering strategy that delicately controls the composition, distribution and magnetism of the 1:2 phase in (Nd0.5 Ce0.5 )30.5 Fe68.5-x Cux B1.0 nanostructured magnets (x = 0–0.5). Experimental studies show that the incorporated Cu enables the formation of a continuous 1:2 GB phase, which is reported for the first time in Nd–Ce–Fe–B nanostructured magnets. More interestingly, the Cu infiltration into the 1:2 phase also permits more Nd to replace Ce, generating a novel Nd-dominated 1:2 phase with a ferro-paramagnetic transformation. A certain fraction of the 1:2 phase with ferromagnetic nature results in an obvious kink near −35 kA/m reversal field at 300 K, which disappears after the ferro-paramagnetic transition at 350 K. At optimal Cu doping (x = 0.2) with a maximized coercivity of 992 kA/m, the paramagnetic and ferromagnetic 1:2 phases coexist with highest total fraction of 4.8 wt%, revealing an advantageous role of paramagnetic 1:2 GB phase in enhancing coercivity. Our exploration paves a novel Cu-mediated approach for rational engineering of the 1:2 GB phase, which may exert far-reaching significance for developing low-cost Nd–Ce–Fe–B PMs. Graphical abstract: Image 1